United States (USA) Economic Policy Towards International Recession - Stanfort, Steven William; Victoria, Ong Argo (Universitas Islam Sultan Agung, 2025)
Abstract. Being a large superpower, the US is not immune from the crisis. In 2008, the US experienced a crisis in its economy. Many economists argue that the economic crisis in the United States which has not completely ended until now was caused by subprime mortgages. This US securities crisis has spread to all corners of the world, Alan Greenspan, former Governor of the US Central Bank said that this financial crisis is an event that occurs once every 100 years,